Government Failure: The Case of Global Environmental Mismanagement - Thomas Andersson (The Research Institute of Industrial Economics (IUI), 1990)
Pollution and polluters can move across national boundaries, but governments which seek to maximize social welfare should coordinate optimal environmental protection through transfer payments or commitments. However, governments may respond to political pressure rather than maximize social welfare, in case the environment is likely to be downgraded due to asymmetric costs, unborn generations, and asymmetries in information. Government failure in one country may reduce the optimal level of cleaning in another country. The findings are applied to atmospheric emissions, deforestation, consumption of tobacco, and the role of mu1tinational corporations. It is suggested that sustainable development should be supported through an international institution which compensates for government failure.
Keywords: F64; Q52; Q58; 330; Environment; Social welfare; Asymmetries